Zwischen Räumen. (Un-)Möglichkeiten von Fremdheit in Henri Nathansens Roman Af Hugo Davids Liv - Räthel, Clemens (Folia Scandinavica Posnaniensia, 2019)
Henri Nathansen’s highly successful bildungsroman Af Hugo Davids Liv, first published in 1917, tells the story of its Jewish protagonist from cradle to grave – with obstacles, adventures and challenges. But much more so, Nathansen offers a multi-layered narration of what it could mean to be a “noble” Jew. Providing a multitude of answers to that question, Af Hugo Davids Liv refuses any definition and thus opens a “third space” in which ambiguous and grained narrations of migration can take place, flourish and be understood in their own right. The article focuses on exploring these narrative interstices and spaces of in-betweenness and in doing so also (re-)discovers Nathansen’s unique way of telling migration as socially always imminent.